2021
DOI: 10.3390/nano11040900
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Nanofiber Based Filters for High Filtration Efficiency Respirators

Abstract: Electrospinning has been used to develop and upscale polyacrylonitrile (PAN) nanofibers as effective aerosol filtration materials for their potential use in respirators. The fibers were deposited onto non-woven spunbond polypropylene (SPP) and the basis weight (grammage, g/m2) was varied to assess the resulting effect on filtration efficiency and breathing resistance of the materials. The results indicated that a basis weight in excess of 0.4 g/m2 of PAN electrospun fibers yielded a filtration efficiency over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…The morphology of the NF layers shows a typical nonwoven stacking structure. The use of nanoscale fibres has proven to be advantageous in air filtration, since their small diameters and high surface-to-volume ratios can enhance the capture of particles through interception and other mechanisms [ 31 , 32 , 33 ]. It has also been shown that homogeneous porosity can result in lower pressure drop due to the slip flow effects of the NFs when compared with microfibre’s counterparts [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The morphology of the NF layers shows a typical nonwoven stacking structure. The use of nanoscale fibres has proven to be advantageous in air filtration, since their small diameters and high surface-to-volume ratios can enhance the capture of particles through interception and other mechanisms [ 31 , 32 , 33 ]. It has also been shown that homogeneous porosity can result in lower pressure drop due to the slip flow effects of the NFs when compared with microfibre’s counterparts [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Different polymeric materials have been used for producing electrospun membrane for filtration including cellulose acetate (CA) [ 37 ], silk fibroin (SF) [ 38 ], poly(lactic acid) (PLA) [ 39 ], polyamide-6 (PA6), poly(vinyl alcohol) (PVA) [ 40 ], polyvinylacetate (PVAc) [ 37 ], polyacrylonitrile (PAN) [ 41 , 42 ], polyvinylidene fluoride (PVDF) [ 43 ], or poly(ethylene terephthalate) (PET) [ 33 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although membranes with higher thickness and basis weight are associated with higher filtration efficiency, they are also associated with higher breathing resistance [6,21]. Thus, a balance should be achieved to obtain the greatest filtration performance and breathability at the same time.…”
Section: Filtration Efficiencymentioning
confidence: 99%
“…In fact, increasing the membranes' thickness provides more opportunities for the particles to meet with the fibers when they are traveling through the membrane [55]. Pardo-Figuerez et al also showed that the percentage of porosity of the electrospun membranes is reduced when a higher basis weight is deposited, which can also contribute to a decrease in breathability [6].…”
Section: Facemask Prototype: Assembling Of the Different Layers And Their Evaluationmentioning
confidence: 99%
See 1 more Smart Citation